Damage standard models with a fixed convex - Cimetiere, A.; Halm, D.; Marigo, J.J.; Molines, E. (Archives of Mechanics, 2005)
The formal structure of a large class of standard damage models is being revisited. Particular attention is paid to the dependence of damage convex on the damage (internal) variables themselves. This dependence complicates the discussion about the existence and uniqueness conditions since the rate of internal variable is no longer a solution of a symmetric variational inequality. The alternative formulation is put forward involving a complementary set of internal variables. This method, leading to a fixed damage convex, brings back the rate response to an incremental behavior relevant to the generalized standard formalism. Some non-fixed convex models are replaced in the framework of damage models with fixed convex.